Red Flag Way: Exploring copyright protection, TRIPS and Open Source software licensing in the People’s Republic of China (Journal of Open Law, Technology & Society, 2013)
The focus of this paper is to explore the interaction between open source software licenses, and China’s developing stance on intellectual property laws and standards over the last three and a half decades.   It is contended that open source software licensing alters the intended use of copyright protection in a manner which conforms to the cultural understandings of the People’s Republic of China. It is also argued that a copyright policy that is preferential towards open source software licensing would advance the PRC’s conformity to TRIPS’ minimum protection requirements.